2018
DOI: 10.18261/issn.2387-5984-2018-01-04
|View full text |Cite
|
Sign up to set email alerts
|

Individuelle behovsvurderinger eller standardiserte tjenestetilbud?

Abstract: En institusjonell etnografi om kommunale saksbehandleres oversettelse fra behov til vedtak Judgements for the individual service user or standardized service?An institutional ethnography on local government administrators' transition from requirements to decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…37 Combined with an increase in government regulations and a tightening of overall resources, each municipality’s flexibility in developing and allocating services has become constrained. 38 In addition, the reduced variation between municipalities can be a result of benchmarking: municipalities trying to adapt to the allocation level of other municipalities by comparing publicly available municipal data. 36 …”
Section: Discussionmentioning
confidence: 99%
“…37 Combined with an increase in government regulations and a tightening of overall resources, each municipality’s flexibility in developing and allocating services has become constrained. 38 In addition, the reduced variation between municipalities can be a result of benchmarking: municipalities trying to adapt to the allocation level of other municipalities by comparing publicly available municipal data. 36 …”
Section: Discussionmentioning
confidence: 99%
“…An ethnographic study demonstrated that institutional guidelines govern the practices of case managers (purchasers) and determine which services will be available to patients. Therefore, case managers play an active role in making assessments to adapt patients' needs to the existing hierarchy of needs (Oydgard, 2018). If the purchaser formulates more general instructions and includes time for additional tasks by recognizing that unforeseen needs can arise, nurses' use of discretion will be acknowledged, and they will be able to address acute and unforeseen events.…”
Section: Discussionmentioning
confidence: 99%
“…Derved kan et menneske ikke betragtes som skarpt afgraenset fra omgivelserne, men må betragtes som en del af et menneskes 'personhed', og det Leibling kalder en 'social, interaktiv hukommelse' (Leibing, 2006:246,253,259-261 (Kröger, 2005). I de seneste årtier har de pårørendes rolle aendret sig på ny; i dag inddrages de pårørende i stor udstraekning som partnere i varetagelse af pleje-og omsorgsopgaver, og de forventes at spille en aktiv rolle (Navne & Wiuff, 2011;Øydgard, 2018 hvoraf to var gruppeinterview med deltagelse af en beboer, en pårørende og en medarbejder. Graden af deltagelse og observation har varieret fra moderat til aktiv deltagelse afhaengig af situationen (Spradley, 1980:58-62) og er dokumenteret i daglige feltnoter.…”
Section: Indledningunclassified